Empowering the tourism community in Gunungkidul using English online and on-site coaching - Dewanti Ratna Pertiwi; Maria Asumpta Deny Kusumaningrum (Institut Teknologi Dirgantara Adisutjipto, 2023)
Tourism is one of a country's potential revenue streams. Gunungkidul district in Yogyakarta province has many natural tourist spots. The locals are thought to be more knowledgeable about the state of tourism, but they cannot speak English. To empower the tourism community after the pandemic, online and on-site coaching for the tourism community was conducted under Dinas Pariwisata of Gunungkidul. SWOT and need analysis were investigated to contribute insightfully to Dinas Pariwisata for future tourism development. In addition, video creations were executed, which consisted of simple expressions and practices with native speakers who are expected to give examples of how to communicate with foreigners. The practices in some potential tourism spots were carried out to encourage the tourism communities to develop their English skill. The results indicated that the tourism communities improved their English skills and confidently communicated with foreigners.